2023
DOI: 10.1007/s10668-023-02918-6
|View full text |Cite
|
Sign up to set email alerts
|

Green merger and acquisition decision driven by environmental regulation and its impact on green innovation: evidence from Chinese heavily polluting listed enterprises

Abstract: How heavily polluting enterprises achieve sustainable development has become an urgent issue to be solved. Based on the data of Chinese heavily polluting listed enterprises during the period of 2010–2020, this paper adopts the probit method to examine how heterogeneous environmental regulations affect green merger and acquisition (GMA) decision, and propensity score matching and difference-in-differences method to explore innovation performance of GMA. The findings are as follows: (1) Command-and-control envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…Thirdly, through grouping regression, it is found that in the year of green M&A, there is a significant positive relationship between green M&A and environmental information disclosure quality in both state-owned enterprise group and non-state-owned enterprise group, but the relationship between green M&A and environmental information disclosure quality in state-owned enterprise group is stronger. Consistent with the research of Fu et al (2022), Zhong and Peng (2022), Sun et al (2023a), they believe that green innovation has a stronger positive impact on state-owned enterprises and they are more willing to take environmental responsibility. However, Zhao et al (2021) believe that due to the natural political connection of state-owned enterprises, they can destroy legitimate interests and avoid illegal punishment, which leads to the weakening of the positive correlation between green M&A and corporate environmental governance.…”
Section: Discussion Of Findingssupporting
confidence: 69%
See 2 more Smart Citations
“…Thirdly, through grouping regression, it is found that in the year of green M&A, there is a significant positive relationship between green M&A and environmental information disclosure quality in both state-owned enterprise group and non-state-owned enterprise group, but the relationship between green M&A and environmental information disclosure quality in state-owned enterprise group is stronger. Consistent with the research of Fu et al (2022), Zhong and Peng (2022), Sun et al (2023a), they believe that green innovation has a stronger positive impact on state-owned enterprises and they are more willing to take environmental responsibility. However, Zhao et al (2021) believe that due to the natural political connection of state-owned enterprises, they can destroy legitimate interests and avoid illegal punishment, which leads to the weakening of the positive correlation between green M&A and corporate environmental governance.…”
Section: Discussion Of Findingssupporting
confidence: 69%
“…Thirdly, previous studies have not reached a consensus on the moderating effect of property rights on the relationship between green M&A and environmental governance, green innovation (Sun et 2023a;Zhao et al, 2021). This study finds (hypothesis 3) that in the year of green M&A, the environmental disclosure quality of both state-owned and non-state-owned enterprises significantly improves.…”
Section: Theoretical Implicationsmentioning
confidence: 71%
See 1 more Smart Citation
“…Currently, green M&A strategies (GMA) are mainly divided into two categories. One is the source emission reduction strategy, which is generally considered to be conducive to the green transformation of enterprises; the other is the terminal governance strategy, which is considered to be detrimental to the green transformation of enterprises [9]. The former refers to the use of green and environmentally friendly means by enterprises during production to reduce pollution emissions.…”
Section: Common Institutional Investors and Green Governancementioning
confidence: 99%
“…proceed below. [9] One possible hypothesis is the "market pressure hypothesis" [10]. In other words, media coverage increases corporate pressure and triggers management shortsightedness.…”
Section: Common Institutional Investors and Green Governancementioning
confidence: 99%